MySQL pocket reference - Reese, George (O'Reilly, 2003)
If you use MySQL, you know why it's the world's most popular open source database: small, fast, and powerful, and so rich in features that no administrator or programmer can stay familiar with all of them. There are always some little-known commands and clauses that could help you become more efficient in your work if you could just keep them in mind. The problem is, you don't always have time to stop and thumb through an exhaustive reference when you're hard at work. If you need a quick reminder, the MySQL Pocket Reference can lead you straight to the answer you need to know to get the job.